The Use of Bring Your Own Device-based Learning to Measure Student Algebraic Thinking Ability - Rudyanto, Hendra Erik; Marsigit, Marsigit; Wangid, Muhammad Nur; Gembong, Sardulo (International Journal of Emerging Technologies in Learning (iJET), 2019)
Many students have algebraic difficulties in learning. This is proven by the fact that students having dif-ficulty facing algebraic elective courses in the 7th semester, where they lack the ability to solve algebraic problems called algebraic thinking skills. This study focuses on finding out the judgment of experts about the use of BYOD-based mathematics knowledge to measure students’ algebraic completion skills. This research applied 3 tests in the control class and treatment class with the reliability of Cronbach to see an increase in the use of BYOD-based learning. Thus, there is an increase in the use of BYOD-based learning to measure students’ algebraic thinking abilities.